Race/ethnicity differences in response to acute antihypertensive treatment of peripartum severe hypertension. (12th December 2022) - Greene, Naomi H.; Pon, Fay F.; Kilpatrick, Sarah J.
Abstract: Background: Hypertensive disorders of pregnancy increase maternal morbidity, mortality, and long-term risk for cardiovascular disease. The rising incidence of chronic hypertension and preeclampsia disproportionately affects people of color. There is a paucity of published data examining differences in the effectiveness of acute antihypertensive agents between pregnant patients of different races/ethnicities. We aimed to determine if the effectiveness of acute antihypertensive agents for peripartum severe hypertension differs by race/ethnicity. Methods: A retrospective cohort study of patients with severe peripartum hypertension (systolic blood pressure ≥ 160 mmHg and/or diastolic blood pressure ≥ 110 mm Hg confirmed within 15 min) to determine whether the effectiveness of blood pressure control using nationally recommended medications (hydralazine, labetalol, nifedipine) differed by race/ethnicity. The primary outcome was reduction and maintenance of blood pressure to target ranges (140–150/90–100 mm Hg or below) for ≥4 h in each race/ethnicity group. Statistical tests included χ 2, Fisher's exact, analysis of variance, and multivariable logistic regression. Results: Of 729 patients receiving treatment for severe peripartum hypertension, all medications were effective (overall 86.4% efficacy) at controlling blood pressure. Labetalol was the most effective medication in White patients (93.0 vs. 74.7% for nifedipine and 86.5% for hydralazine, p  < .001). No overall differences in medication effectiveness were found in Black, Asian, or LatinX patients. Black and Asian patients were more likely to experience >1 hypertensive episode [51.0 and 49.0%, respectively vs. 35.4% (White) and 40.0% (LatinX), p  = .008]. Conclusion: Currently recommended therapies for severe peripartum hypertension are effective in controlling blood pressure for ≥4 h in patients of all race/ethnic groups. Labetalol was the most effective medication in White patients with no overall differences in medication effectiveness in Black, Asian, or LatinX patients.